2016
DOI: 10.1007/s13361-016-1510-1
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Sequence Ion Selectivity: Proline versus Pipecolic-acid-containing Protonated Peptides

Abstract: Substitution of proline by pipecolic acid, the six-membered ring congener of proline, results in vastly different tandem mass spectra. The well-known proline effect is eliminated and amide bond cleavage C-terminal to pipecolic acid dominates instead. Why do these two ostensibly similar residues produce dramatically differing spectra? Recent evidence indicates that the proton affinities of these residues are similar, so are unlikely to explain the result [Raulfs et al., J. Am. Soc. Mass Spectrom. 25, 1705-1715 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Relative energies of amide N protonated structures, transition states, and fragment proton‐bound dimers (PBD) were calculated and shown in Scheme S1 (Supporting Information). The Ala‐Pro amide N (Nc(S), in which c represents the third amide bond and S denotes the absolute configuration of the proline nitrogen atom) was indeed the energetically most favored amide nitrogen protonation site. While the b 3 ‐y 3 fragmentation pathway was energetically preferred, the difference between the energy barriers of different [AAAPAA+H] + dissociation pathways was less than 2.3 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative energies of amide N protonated structures, transition states, and fragment proton‐bound dimers (PBD) were calculated and shown in Scheme S1 (Supporting Information). The Ala‐Pro amide N (Nc(S), in which c represents the third amide bond and S denotes the absolute configuration of the proline nitrogen atom) was indeed the energetically most favored amide nitrogen protonation site. While the b 3 ‐y 3 fragmentation pathway was energetically preferred, the difference between the energy barriers of different [AAAPAA+H] + dissociation pathways was less than 2.3 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…Breci and coworkers analyzed the fragmentation data of doubly charged peptides in database, and concluded that the side chain of the adjacent residue to Pro played a role in the cleavage of the Xxx‐Pro bond via restricting the conformation of the proline‐containing peptides . Recently, in the theoretical study of proline and pipecolic‐acid‐containing protonated peptides, Abutokaikah et al suggested that the stability of transition structures was directly affected by ring type and stereochemistry, and therefore differing the production distribution under low‐energy CID condition . Despite the progress above in understanding the proline effect, the mechanism of the N‐terminal adjacent basic residues suppressing the selective cleavage of proline remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is similar to fragmenting proline-and/or pipecolic acidcontaining peptides. 61 Both proline and pipecolic acid contain a secondary amide bond, which is similar to the amide bonds in peptoids. Cleavage of the amide bond C-terminal to both residues will lead to a N-terminal oxazolone fragment with a fixed charge, and formation of the corresponding peptide y-ion will require transferring a non-mobile proton from the N-terminal fragment to the C-terminal fragment.…”
Section: Scheme 5 Proposed Fragmentation Mechanism For Singly-protonated Peptoidsmentioning
confidence: 97%
“…62 Both effects and related observations have been welldocumented in the literature. 57,[61][62][63][64][65][66] Our previous experiments using deuterium labeled peptoids suggest that the Y-ions contain a hydrogen atom abstracted from the C-Hα bond adjunction to the dissociating amide bond, which would correspond to mode A. An example of the formation of Y3 and Y4 from This article is protected by copyright.…”
Section: Scheme 5 Proposed Fragmentation Mechanism For Singly-protonated Peptoidsmentioning
confidence: 99%